Faktor-Faktor yang Berpengaruh terhadap Pengambilan Keputusan Wanita Migran Bermigrasi ke Kota Malang - Budijanto, B (Forum Geografi, 2011)
The low family income, lack of job vacancy other than farmland, the narrow square of land possession, and the high level of household load encourage women deciding to migrate to Malang as an effort to support their household economic welfare improvement. The aim of this research is to find and reveal any condition which causes migrant women household to decide migrating to Malang. The research result shows that demography variables (age, marriage status, and the amount of household load) have significant effect toward migrant womens decision making to migrate to Malang. Also, social-economic variable (migrant women education, household income, farmland square, and type of the job) affects migrant womens decision making to migrate to Malang significantly; but, job vacancy in origin area does not bring significant effect toward migrant womens decision making to migrate to Malang.